2022
DOI: 10.2147/jir.s380785
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lycopene Administration Attenuates Inflammation and Oxidative Stress by Regulating Plasma Lipids in Rats with Lipopolysaccharide-Induced Epididymitis

Abstract: Purpose Epididymitis histological alterations and related long-term reproductive issues cannot be cured by antibiotics alone. Few studies have been done on the effect of lycopene on epididymitis, despite the fact that it is an efficient antioxidant. The objective of this study was to assess the impact of lycopene on Lipopolysaccharide (LPS)-induced epididymis and lipid metabolism. Methods Thirty-one 260–290g rats were separated into the blank control group (n=10), the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our other study revealed a correlation between LPS-induced differential lipids and cytokines and oxidative status indicators, indicating that the regulation of lipid content and composition to cytokines and oxidative status is the potential pathway to control epididymis inflammation and oxidative stress injury. 21 In this research, we studied the testis lipidomics, which were differentially regulated during LPS-induced systemic inflammation, including Cer, Hex2cer, DG, LPC, LPE, LPG, MG, PC, PE, PG, PI, PS, SM, TG. This forced regulation concerned the testis cytokines and ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Our other study revealed a correlation between LPS-induced differential lipids and cytokines and oxidative status indicators, indicating that the regulation of lipid content and composition to cytokines and oxidative status is the potential pathway to control epididymis inflammation and oxidative stress injury. 21 In this research, we studied the testis lipidomics, which were differentially regulated during LPS-induced systemic inflammation, including Cer, Hex2cer, DG, LPC, LPE, LPG, MG, PC, PE, PG, PI, PS, SM, TG. This forced regulation concerned the testis cytokines and ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…LYC was found to attenuate LPS-induced epididymis injury in our previous study. And its regulatory mechanism is related to the changes of plasma lipidome (22). The present study evaluated the protective effects of LYC against impaired testicular function caused by LPSinduced systemic inflammation.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 97%
“…It is a bright red pigment that gives tomatoes their distinct color [33]. Lycopene has been extensively studied over the past few decades for its ability to attenuate inflammation and oxidative stress [34].…”
Section: Lycopenementioning
confidence: 99%